(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Food as a cultural marker in literature provides a unique lens for examining complex themes of identity, heritage, and resistance, particularly within postcolonial contexts. In postcolonial literature, food frequently emerges more than a mere sustenance or tradition; it becomes a powerful metaphor for cultural expression, adaptation, and resilience. As Appadurai (1988) notes in his influential work on food and identity, cuisine can serve as an archive of social memory, preserving cultural resilience and community bonds. This sentiment resonates strongly in postcolonial literary studies, where food often acts as a conduit of both personal and communal identity. In the wake of colonial disruption, food takes on deeper, nuanced meanings, symbolising the enduring struggle to reclaim and redefine one’s heritage in a world shaped by colonial histories and contemporary global influences.